Inovasi Modul Digital Pembelajaran Business Planning: Suatu Upaya Penguatan Pendidikan Kewirausahaan di Universitas Andalas - Donard Games; Berri Brilliant Albar; Ares Albirru Amsal (Warta Pengabdian Andalas, 2021)
Entrepreneurship education has played a crucial role in enhancing entrepreneurship in university. Technological changes and recent pandemic crises have accelerated a new method to enhance the effectiveness of entrepreneurship education. Business planning is an essential document that should be mastered by students as this would help them formulate and implement business plans or strategies. Universitas Andalas has committed to stimulating entrepreneurship courses as mandatory for all of its faculties. This time is a moment to renew how to learn business planning effectively, and this can be conducted by providing video production that includes insights from the business world. We have implemented this point of view in the context of Universitas Andalas, resulting in more engagement and understanding of students regarding business planning.